Treatment-related toxicity and improved outcome from immunotherapy in hepatocellular cancer: Evidence from an FDA pooled analysis of landmark clinical trials with validation from routine practice. (November 2021) - Pinato, David J.; Marron, Thomas U.; Mishra-Kalyani, Pallavi Shruti; Gong, Yutao; Wei, Guo; Szafron, David; Sharon, Elad; Saeed, Anwaar; Jun, Tomi; Dharmapuri, Sirish; Naqash, Abdul R.; Peeraphatdit, Thoetchai; et al.
Abstract: Purpose: The development of treatment-related adverse events (trAE) correlates favorably with clinical outcomes in multiple studies of patients receiving immune checkpoint inhibitors (ICI); however, this relationship is undefined in patients with hepatocellular carcinoma (HCC). Patients and methods: We derived a cohort of 406 patients with unresectable/advanced HCC receiving ICI therapy as part of international clinical trials submitted to the US Food and Drug Administration (FDA) in support of marketing applications. We tested whether the development of clinically significant trAE (i.e. graded ≥2, trAE2) predicted improved overall survival (OS), progression-free survival (PFS), and objective response rates (ORR) following ICI. We established an international consortium of 10 tertiary-care referral centres located in Europe (n = 67), United States (US, n = 248) and Asia (n = 42) to validate this association. Results: In the FDA dataset of 406 patients, 325 (80%) with Barcelona Clinic Liver Cancer (BCLC) stage C HCC mostly treated with ICI monotherapy (n = 258, 64%), trAE2 were reported in 228 patients (56.1%). Development of trAE2 was associated with longer OS (16.7 versus 11.2 months) and PFS (5.5 versus 2.2 months) and persisted as an independent predictor of outcome after adjusting for viral aetiology, gender, Child-Pugh class, BCLC stage, AFP levels, ECOG-PS, ICI regimen (mono/combination therapy) and receipt of corticosteroid therapy. In a multi-institutional cohort of 357 patients with similar characteristics mostly treated with ICI monotherapy (n = 304, 85%), the development of trAE2 was associated with longer OS (23.3 versus 12.1 months) and PFS (9.6 versus 3.9 months). TrAE2 were confirmed predictors of improved OS (HR 0.43; 95% CI:0.25–0.75) and PFS (HR 0.48; 95% CI: 0.31–0.75), with multivariable analyses confirming their association with outcome independent of clinicopathologic features of interest. Additional time-varying multivariable analyses also indicated that trAEs were associated with a decreased risk of progression (HR 0.56, 95% CI: 0.46–0.67) in the FDA dataset and death (HR 0.55; 95% CI: 0.32–0.95) in the multi-institutional dataset. Conclusion: Development of trAE2 correlates with improved outcomes in patients with HCC receiving ICI in clinical trials and in routine practice. Prospective studies aimed at understanding the underlying immunologic foundations of such relationships are warranted to identify predictive biomarkers of toxicity and response. Highlights: Treatment-related adverse events (trAEs) may affect immunotherapy outcomes in HCC. We correlated trAEs with response and survival in independent datasets. trAEs predict for better response and survival in trials and clinical practice.